If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(5x + -2) = 4(2x + 3) Reorder the terms: 2(-2 + 5x) = 4(2x + 3) (-2 * 2 + 5x * 2) = 4(2x + 3) (-4 + 10x) = 4(2x + 3) Reorder the terms: -4 + 10x = 4(3 + 2x) -4 + 10x = (3 * 4 + 2x * 4) -4 + 10x = (12 + 8x) Solving -4 + 10x = 12 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -4 + 10x + -8x = 12 + 8x + -8x Combine like terms: 10x + -8x = 2x -4 + 2x = 12 + 8x + -8x Combine like terms: 8x + -8x = 0 -4 + 2x = 12 + 0 -4 + 2x = 12 Add '4' to each side of the equation. -4 + 4 + 2x = 12 + 4 Combine like terms: -4 + 4 = 0 0 + 2x = 12 + 4 2x = 12 + 4 Combine like terms: 12 + 4 = 16 2x = 16 Divide each side by '2'. x = 8 Simplifying x = 8
| 4x-(x+2)=11x | | 7x+1-6x+x+2= | | 13x-(22-5x)=4(3x+5) | | (-5)*8= | | -65-2x=5-2x | | 6*(-8)= | | 176-3x=42x+21 | | 14-8x=50-15x | | 20x-10-[5(3x+1)-3(6x-5)]-5(6x+1)=0 | | 12-(-3)= | | 83-[9*(-3)]= | | 83-[9X(-3)]= | | 12*z= | | (a+2)(a+7)=0 | | 21w^2+35w=0 | | (-6)x(-4)x(-8)= | | 3a^2+18a=0 | | 85-(-62)-95= | | p^2-3p=0 | | 3-9h+1x=-12 | | 63+(-108)-(-23)= | | 25+(-67)-22= | | 268-372*53(9+74)= | | (-94)+(-77)-(-11)= | | 34-19-(43)= | | 46+(-17)-(-12)= | | 99-3x=15x+23 | | 50+30x=2*x^2 | | (-35)-(-62)= | | 2x+11=-70-7x | | 3-7y=-18 | | 41+(-46)= |